Phase-Controlled Planar Metalenses for High-Resolution Terahertz Focusing - Xin Yu (Photonics, 2021)
We experimentally demonstrate that high-resolution terahertz focusing can be realized in planar metalenses, which consist of arrays of different V-shaped antenna units on a silicon substrate. Numerical results show that a larger numerical aperture of metalenses can provide smaller full width at half maximum of field distribution, leading to higher spatial resolution. The measurement of fabricated metalenses samples was performed by a terahertz near-field imaging system, and experimental results agree well with the numerical prediction. Especially for 1.1 THz incident light, when the numerical aperture increases from 0.79 to 0.95, the full width at half maximum correspondingly decreases from 343 μm to 206 μm, offering an improvement of spatial resolution.